Strategies and Future Opportunities for the Prevention, Diagnosis, and Management of Cow Milk Allergy - Zepeda-Ortega, Benjamin; Goh, Anne; Xepapadaki, Paraskevi; Sprikkelman, Aline; Nicolaou, Nicolaos; Hernandez, Rosa Elena Huerta; Latiff, Amir Hamzah Abdul; Yat, Miu Ting; Diab, Mohamed; Hussaini, Bakr Al; Setiabudiawan, Budi; Kudla, Urszula; et al. (Frontiers in Immunology, 2021)
The prevalence of food allergy has increased over the last 20-30 years, including cow milk allergy (CMA) which is one of the most common causes of infant food allergy. International allergy experts met in 2019 to discuss broad topics in allergy prevention and management of CMA including current challenges and future opportunities. The highlights of the meeting combined with recently published developments are presented here. Primary prevention of CMA should start from pre-pregnancy with a focus on a healthy lifestyle and food diversity to ensure adequate transfer of inhibitory IgG- allergen immune complexes across the placenta especially in mothers with a history of allergic diseases and planned c-section delivery. For non-breastfed infants, there is controversy about the preventive role of partially hydrolysed formulae (pHF) despite some evidence of health economic benefits among those with a family history of allergy. Clinical management of CMA consists of secondary prevention with a focus on the development of early oral tolerance. The use of extensive Hydrolysate Formulae (eHF) is the nutrition of choice for the majority of non-breastfed infants with CMA; potentially with pre-, probiotics and LCPUFA to support early oral tolerance induction. Future opportunities are, among others, pre- and probiotics supplementation for mothers and high-risk infants for the primary prevention of CMA. A controlled prospective study implementing a step-down milk formulae ladder with various degrees of hydrolysate is proposed for food challenges and early development of oral tolerance. This provides a more precise gradation of milk protein exposure than those currently recommended.